2021
DOI: 10.3389/fvets.2021.708597
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Supplementation of Macleaya cordata Extract and Benzoic Acid on the Growth Performance, Immune Responses, Antioxidant Capacity, Intestinal Morphology, and Microbial Composition in Weaned Piglets

Abstract: Because the use of antibiotics is forbidden, piglets experience a considerable weanling stress, resulting in increased incidence of diarrhea and death. Macleaya cordata extract or benzoic acid have anti-inflammatory, antioxidant, and antimicrobial activities that makes them potential antibiotic alternatives. The objective of this study was to evaluate the potential effects of feed supplemented with Macleaya cordata extract and benzoic acid on growth performance, immunity, antioxidant capacity, intestinal morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 71 publications
1
20
0
Order By: Relevance
“…The reduction in body weight can be attributed to a reduction in feed intake. Supplementation with MCE has been shown to improve performance and immune function in weaning pigs, Xuefeng black-bone chicken, and Pacific White Shrimp [ 25 , 34 , 35 ]. However, the effects of MCE on animal performance were not identical in different experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction in body weight can be attributed to a reduction in feed intake. Supplementation with MCE has been shown to improve performance and immune function in weaning pigs, Xuefeng black-bone chicken, and Pacific White Shrimp [ 25 , 34 , 35 ]. However, the effects of MCE on animal performance were not identical in different experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of MCE on animal performance were not identical in different experiments. It has been reported that dietary MCE administration increased the Final BW and ADG, and the reduced feed efficiency and diarrhea rate in weaned piglets [ 25 ]. Moreover, diets with 0.15 g/kg of MCE increased the feed intake and weight gain on day 24 and day 35, and improved FCR, flock uniformity, and breast meat yield on day 35 in broilers with necrotizing enteritis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the addition of MCE to the feed significantly elevated the serum levels of IgA and IgM. Wang et al ( 33 ) also reported that MCE supplementation could increase serum concentrations of IgA and IgM. Serum IgA and IgM are important parts of humoral immunity ( 34 ).…”
Section: Discussionmentioning
confidence: 54%
“…Measurements of villus height and crypt depth were taken only from sections where the plane of section ran vertically from the tip of villus to the base of an adjacent crypt by using a light microscope. Ten well-oriented villus × 3 sections of each pig were used to determine these indices (Wang et al, 2021).…”
Section: Morphology Of Small Intestinementioning
confidence: 99%